Penerapan Aspek Keselamatan Perkeretaapian pada PT.KAI (Persero) Daop IV Semarang - Tiarma Lubis; Evi Widowati (Dian Nuswantoro Semarang, 2017)
Railways is everything related to facility, infrastructure, human resource and train supporting facility for the operation of railway transport. The production of passenger trains during the years 2010-2014 in the Java island has increased by 8.29% annually. The railway accidents frequency are inluenced by: human factors, infrastructure factors, facility factors, operational factors, and external factors. This research aims to know the description of the aspects of railwaysafety application at PT. KAI (Persero) DAOP IV Semarang. This was evaluative research.The result showed that of the 253 points of the aspects of railways safety, as much as 235 (93%) points were accordance to standard, 13 (5%) points were not accordance tostandard, and 5(2%) did not conform to standard.The recommendation are fulillments of the safety railway aspects such as: increase the crossing-guard offifcer who have a competency certiicate, provide training and education for certiication of compentence for pcrossing-guard oicer that have not been certiied, facilitating the station with ire protection system, awarding and recoloring of secure border from railways on the station platform, and marking the installation of portable ire extinguisher.Keywods : railway, safety